Adult Onset Still's Disease Associated with Mycoplasma pneumoniae Infection and Hemophagocytic Lymphohistiocytosis. (26th October 2016) - Agnihotri, Abhishek; Ruff, Allison; Gotterer, Lauren; Walker, Addie; McKenney, Amy H.; Brateanu, Andrei
Abstract : Adult Onset Still's Disease (AOSD) is a systemic inflammatory disorder that can be associated with hemophagocytic lymphohistiocytosis (HLH), a rare but potentially fatal disease of overactive histiocytes and lymphocytes. We present a unique case of AOSD complicated by Mycoplasma pneumonia infection and HLH. A 28-year-old female developed joint pains followed by a diffuse, erythematous, pruritic skin rash that quickly spread throughout the body. The patient deteriorated and developed fever, chills, cough, and dyspnea and had to be intubated. She had hypoalbuminemia, elevated liver enzymes, a very high serum ferritin level, positive anti- Mycoplasma pneumonia IgG and IgM antibodies, and normal rheumatoid factor and anti-nuclear antibodies. The chest X-ray showed diffuse bilateral infiltrates. Bone marrow biopsy revealed hemophagocytosis. The patient was treated with azithromycin, methylprednisolone, and anakinra and was discharged home on cyclosporine and prednisone. This case highlights that patients can develop features of both AOSD and HLH at the beginning of the disease and early diagnosis and treatment increase the likelihood of recovery.